2010
DOI: 10.1111/j.1439-0442.1970.tb00789.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the “Prostate test” in Checking the Administration of Oestrogens in the Calf1

Abstract: Summary The effect of various oestrogens was studied in male calves. The following oestrogens were used: diethylstilboestrol (in dosages of 20, 50 and 80 mg.), hexoestrol (80 and 160 mg.), dienoestrol (80 mg.) and oestradiol monobenzoate (80 mg.). The histological reaction of the prostate was studied in short term experiments (1–21 days after administration of the oestrogen) and long term experiments (8, 9, and 12 weeks after administration of the oestrogen). The oestrogens were injected both intramuscularly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…After both parenteral and oral administration of oestrogens hyperplastic and metaplastic changes of the prostate were found. These changes have already been described in earlier papers (RUITENBERG et al, 1969(RUITENBERG et al, , 1970KROES, 1970).…”
Section: Description Of the Oestrogen-induced Changes In The Various supporting
confidence: 75%
“…After both parenteral and oral administration of oestrogens hyperplastic and metaplastic changes of the prostate were found. These changes have already been described in earlier papers (RUITENBERG et al, 1969(RUITENBERG et al, , 1970KROES, 1970).…”
Section: Description Of the Oestrogen-induced Changes In The Various supporting
confidence: 75%
“…The present study examined a novel detection strategy based on PR expression in the male accessory sex glands in response to 17β-oestradiol administration to reveal growth promoter abuse. In this study, besides inducing typical epithelial hyperplastic and metaplastic changes observed in the prostate, urethra and bulbourethral gland (Ruitenberg and others 1970, Kroes and others 1971, Hendry and others 1985) and testis atrophy (Noorafshan and others 2005), 17β-oestradiol induced significant transcriptional upregulation of PR cDNA in the prostate (7.5- and 16-fold increases, respectively) and particularly in the bulbourethral gland (39- and 429-fold increases, respectively) in the animals from groups A and B. These results demonstrate that 17β-oestradiol specifically induced transcriptional regulation of PR cDNA in the prostate and bulbourethral glands of animals in groups A and B, while no changes in PR transcription were observed in these tissue types in animals from group C, which shows that PR is specifically upregulated by 17β-oestradiol in the prostate and the bulbourethral glands in a dose-dependent way.…”
Section: Discussionmentioning
confidence: 83%
“…In earlier publications (RUITENBERG, KROES, BERKVENS, 1969, 1970 the histological examination of the prostate was described as a method for the detection of estrogen administered to male calves since the administration of estrogens to calves is forbidden by law in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%